Penerapan Penilaian Berbasis Kelas dan Penilaian Portofolio dalam Menumbuhkan Minat Baca di SDN Daan Mogot 1 Tangerang Kecamatan Tangerang - Ina Magdalena; Lutfiatun Nafisah; Nova Inka Tripalupi; Siti Humairoh (RC-INSTITUT, 2020)
This article discusses the use of class and portfolio assessments in developing students’ interest in reading. The research method used is a description of portfolio instruments, observation, and interviews. The study was conducted at Daan Mogot 1 School in Tangerang, from Juli 2020. Portfolios of twenty-eight of 6th-grade students were used. In addition to using portfolios, data were also obtained from library staff and teachers. The data in the study were the titles of books read by the students, the titles they wanted, and the efforts made by schools and teachers in increasing reading interest. The results show that students' interest in reading was good. The average number of books read in the past year is 6 titles consisting of various books, commonly storybooks, or stories. The program conducted to develop reading interest is visiting the school library every Monday from 1 to 2.30 pm. However, the data taken from the last two months reveal that students’ interest in visiting the library is not satisfying, only 7 students came to visit and read in the library.